Factors affecting local leaders' perception on the adaptation ability of Malaysian small scale fishermen towards climate change - Man, Norsida; Sahharudin, Nor Farhana; Abu Samah, Asnarulkhadi; Mohamed Shaffril, Hayrol Azril (Human Resource Management Academic Research Society, 2017)
This study attempts to examine factors that affect local leaders’ perception on the adaptation ability of small scale fishermen towards climate change. This study is quantitative in nature and via multi-stage cluster sampling, a total of 300 respondents from two fisheries districts were selected. The analysis demonstrates a significant difference between the group leaders’ perception towards small scale fishermen’s ability to adapt while factors such as age and income was recorded to have a significant relationship with their perception towards small scale fishermen’s adaptation ability towards climate change. A number of discussions have been highlighted and hopefully it can be a good addition to the existing literature.